MAKNA IKLAN CETAK INDOVISION VERSI â€œMENGAPA MEMILIH INDOVISION?â€ DI SURATKABAR KOMPAS - Erna Mariana Susilowardhani (Sociae Polites, 2015)
AbstractAdvertisement as a tool to convey message of aproduct has been a must in the business world. Thestrong competition beetwen products makes theproducer has to design special promotion strategycarefully, especially through advertisement in themass media. Indovision as a TV cable provider alsopose an advertisement in mass media in the formof messsage as a construction result of what theproducer want to communicate to the mass. Thisresearch want to analyse the meaning of symbol ofmessage on the printed advertisement of theIndovision version of â€œWhy choose Indovision?â€ byusing concepts of advertising, advertising media,semiotics and theory of reality construction byusing descriptive explorative approach. The unit ofanalysis will cover all elements which is find in thatprinted advertisement on Kompas, at Saturday,October 4th, 2014. The research shows that printedadvertisement of Indovision version â€œWhy chooseIndovision?â€ is using comparative interest throughpicture appearance in the television screen thatIndovision is providing distinct and clearer picturecompare to other brand especially during badweather although the price of reguler subscriptionis more expensive.Keywords: advertisement meaning, Indovisionprinted advertisement, Semiotics, RealityConstruction in the advertisement AbstrakIklan sebagai sarana penyampaian pesan bagiproduk sudah menjadi keharusan dalam duniabisnis. Kompetisi antar produk yang ketatmembuat para produsen harus merancang strategipromosi secara seksama, terutama melalui iklan dimedia massa. Indovision, sebagai penyedia jasatelevisi berlangganan juga memuat iklan di mediamassa dalam bentuk pesan sebagai hasilkonstruksi yang ingin disampaikan produsenkepada khalayak. Penelitian ini ingin menganalisismakna dari lambang pesan pada iklan cetakIndovision versi â€œMengapa Memilih Indovison?â€dengan menggunakan konsep periklanan, mediaperiklanan, semiotika dan teori konstruksi realitasdengan pendekatan deskriptif eksploratif. Unitanalisis mencakup semua unsur yang terdapatdalam iklan cetak tersebut yang dimuat padaKompas, Sabtu 4 Oktober 2014. Hasil penelitianmenunjukkan bahwa iklan cetak Indovision versiâ€œMengapa Memilih Indovision?â€ menggunakandaya tarik komparatif melalui tampilan gambar dilayar televisi bahwa Indovision memberikangambar yang lebih jelas dan jernih dibandingkanmerek lain terutama saat cuaca buruk meskipunharga langganan lebih mahal.Kata kunci: Makna Iklan, Iklan cetak Indovision,Semiotika, Konstruksi Realitas dalam Iklan.